Undergraduate econometrics - Carter Hill; William Griffiths; George Judge (USA Wiley & Sons, Inc., 1998)
This book explores econometrics using an intuitive approach that begins with an economic model. It emphasizes motivation, understanding, and implementation and shows readers how economic data are used with economic and statistical models as a basis for estimating key economic parameters, testing economic hypotheses and predicting economic outcomes.
Donated by: Anvar Hodjaev
Keywords: Econometrics